(untitled) (Scientific journal of the Fergana State University, 2023)
In this article, the image of Yusuf, which is widespread in Eastern classical literature, in particular, the artistic interpretation of this image in the work of Shah and poet Umarkhan Amiri, the founder of the Koqan literary environment, is covered based on the analysis. Psychological, system-structural, comparative-typological methods were used in the research. As a result, the thoughts about the poet were summarized and completed. Amiri’s use of words is unique and provides the basis for many studies.